PROTEIN FROM JAWLA (ACETES SPP.) AND SQUILLA (ORATO SQUILLA NEPA) - GARG, D K; NAIR, A LEKSHMY; PRABHU, P V (Fishery Technology, 2017)
A simple method of isolation of protein from jawla prawn and squilla, which does not involve any chemical treatment, is reported. The method consists in blending the jawla prawn/ squilla with equal quantity of water, removal of chitinous matter, heating the pulp at ll2Â°C for 15-20 minutes and drying the precipitated protein after filtration.